قباء اور اہل قباء کی ثقافت،مذاہب اورطرز تعمیر:ایک تاریخی مطالعہ: Quba and Its People, A Historical Overview of Their Culture, Religions and Architecture (Al Basirah, 2025)
Abstract:This study explores the historical, cultural, and religious significance of Quba, a prominent early Islamic settlement located near Madinah. It was the first place where the Prophet Muhammad (PBUH) stayed following the Hijrah. Before the advent of Islam, it was inhabited by a range of Arab and Jewish tribes practicing various religions, including idolatry, Judaism, and Christianity. Revisiting the already available literature one can find that although various scholars have focused on the masjid e Quba and the stay of Prophet PBUH there, for example a thesis is written about the inhabitance of Masjed e Quba in the early Islam discusses the construction of it in detail. Another thesis "The Route of the Prophet's Migration from Quba to Madinah" states the journey of migration in detail, but detailed information about the Quba region and the people living there especially about their culture, religion and architecture is still lacking.  Adopting qualitative research methodology, the study explores the region’s socio-cultural landscape, tribal dynamics, and the peaceful coexistence of religious communities. It offers a detailed analysis of Quba’s architectural structures, including defensive forts, residential buildings, and public wells, which reveal the community’s adaptation to environmental and strategic needs. It shows the role of marketplaces as hubs of trade and interaction. The research also highlights the settlement’s literary inclinations, particularly in poetry. Through a historical and analytical approach grounded in classical sources, the paper argues that Quba was more than a temporary resting point, it was a model of early Islamic community life. Its structured urban layout, social diversity, and cultural richness contributed significantly to the foundational phase of the Islamic civilization. The findings contribute to broader discourses on early Islamic urbanism, tribal cooperation, and the integration of religious and social identities.
Keywords: Prophet (PBUH); Quba; Islamic Architecture; Islamic History; Arabic Culture; Pre Islamic Religions